"A View from Old Age': Women's Lives as Narrated Through Objects. Issue 1 (2nd January 2019) - Hannan, Leonie; Carney, Gemma; Devine, Paula; Hodge, Gemma
ABSTRACT: This article uses interview data gathered during a collaborative cross-disciplinary project undertaken in 2016 to explore experiences of longevity in qualitative detail with a small cohort of Northern Irish participants. The project was inspired by Penelope Lively's autobiography Ammonites and Leaping Fish: A Life in Time (2013, 4, 199), which documents the author's feelings about her life through focused reflections on her own possessions. Lively chose objects which she felt "oddly identified" her life and proposed that "people's possessions speak of them". We devised a series of activities to be undertaken with participants over the age of 60, with the intention of using material things as a lens on longevity. In this article we use interview data with three female participants to analyse women's narration of their own biographies. The aim of this article is to explore the role of the possessions in narrating women's lives and to consider how themes of ageing, memory, relationships, and the self are articulated through objects. The theoretical context for this exploratory work refers to cultural gerontology, material culture studies, gender studies and scholarship on life history. We conclude that objects offer a useful, tangible means of articulating and communicating the complexity of women's longevity.